2015
DOI: 10.1370/afm.1711
|View full text |Cite
|
Sign up to set email alerts
|

It's Time to Shine the Light on Direct-to-Consumer Advertising

Abstract: Pharmaceutical marketing is undergoing a transition as the business, delivery, and consumption of health care have increasingly become part of a growing digital landscape. Changes in pharmaceutical promotion also coincide with federal "sunshine" regulations newly implemented under the Affordable Care Act that require disclosure of certain marketing and industry payments to physicians. Collectively, these trends could lead to fundamental shifts in physician-directed and direct-to-consumer advertising (DTCA) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…13 Yet this marketing medium remains highly controversial given the rising costs of prescription drugs, a point underscored by a recent vote by the American Medical Association in support of a DTCA ban. 39 Despite eDTCA's rapid growth and maturation, regulatory responses seem to be several steps behind industry activities, who can no longer afford to wait for FDA to give them sufficient guidance on how to engage with their patients online.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Yet this marketing medium remains highly controversial given the rising costs of prescription drugs, a point underscored by a recent vote by the American Medical Association in support of a DTCA ban. 39 Despite eDTCA's rapid growth and maturation, regulatory responses seem to be several steps behind industry activities, who can no longer afford to wait for FDA to give them sufficient guidance on how to engage with their patients online.…”
Section: Discussionmentioning
confidence: 99%
“…11 This means that continued growth in US national prescription drug spending will likely fuel further spending on DTCA, especially given increased scrutiny to physician-directed promotion due to transparency requirements enacted as part of the ACA. 6,12,13 Within the overall category of DTCA, a recent study found that Internetbased DTCA was the only subcategory that experienced rapid growth (an estimated 109% increase) from [2005][2006][2007][2008][2009]. 2 Yet, the ascendance of eDTCA should come as no surprise, with surveys conducted by the Pew Research Center showing that 72% of Internet users actively search for health information online.…”
Section: Future Growth Of Edtcamentioning
confidence: 99%
“…Nevertheless, given that DTCA is legally permissible in the United States and it is unlikely that this will be reversed, Kim's recommendation for more comprehensive guidelines for online prescription drug promotion needs to be heeded. The increasing pervasiveness of digital communication will mean drug marketers will continue to adopt innovative e-DTCA tactics 12 and guidelines must be flexible enough to keep abreast of and adequately account for developments in online drug promotion. For this to be achieved, more will need to be known about how pharmaceutical companies are adapting DTCA to the online environment.…”
mentioning
confidence: 99%
“…For this to be achieved, more will need to be known about how pharmaceutical companies are adapting DTCA to the online environment. As Mackey and Liang 12 have noted, here lies the most urgent challenge in ensuring that DTCA is more productive than problematic, compelling pharmaceutical companies to be more transparent about what they are doing and spending when 'informing' consumers.…”
mentioning
confidence: 99%
“…13 An essay identifies potential impending shifts in both physician-directed and direct-to-consumer advertising due to new federal "Sunshine" regulations that require disclosure of certain marketing and industry payments to physicians. 14 This issue contains a disquieting study that delineates the limited availability of physicians in rural areas who can prescribe buprenorphine for opioid use disorder. 15 The study addresses issues of rural health care delivery, opioid addiction, and creating a rational and effective health care workforce, that have been addressed with rigor and perspective over many years by the lead author, Roger Rosenblatt.…”
mentioning
confidence: 99%